Clinical Quiz-Newborn Female with an Anorectal Malformation and a Gynecological Abnormality - Anisha Apte; Allison Mayhew; Elise McKenna; Veronica Gomez-Lobo; Marc A. Levitt (Georg Thieme Verlag KG, 2022)
We present a case of a newborn female with imperforate anus who on exam was found to have a rectal fistula in the vestibule, no vaginal opening, and a normal urethra. A diagnostic laparoscopy was performed to elucidate the internal anatomy. The case is presented with a focus on surgical strategies in approaching the female patient with anorectal malformation and a Mullerian anomaly, with questions for the readers posed in a quiz format.